Peningkatan Pengetahuan Masyarakat terhadap Riwayat Penggunaan Napza di Wilayah Kerja Puskesmas Kuranji - Edo Gusdiansyah; Welly Welly (Warta Pengabdian Andalas)
Narcotics and alcohol abuse is a health problem and a new thing of concern and is contained in the SDGs, namely ensuring a healthy life and promoting prosperity for all people of all ages. In 2021, around 269 million people worldwide abused drugs, while in Indonesia; there were 1,307 people (833 cases). Factors causing drug use are individual, environmental, and family, ranging from trial and error to curiosity, dependence, and distribution. The negative impact on society is medical, social, legal, economic, and security. The engagement community activity aimed to increase public knowledge of drug use history and provide health education. It was provided with two meetings and demonstrations of various drugs. Efforts given to patients who use drugs were counselling therapy and supportive psychotherapy. This activity was carried out on January 25-26, 2023, with 20 participants. The evaluation results showed increased adolescent knowledge about the dangers of drugs, family roles, and parenting styles based on the pretest and posttest. Suggestions for the health centre are to monitor the results of this education.